IMPACT OF DIABETES MELLITUS ON SEVERITY OF MELIOIDOSIS INFECTION IN TEMERLOH: A RETROSPECTIVE STUDY - Maria, AB Dorothy; Tan, Justin YK; Normala, N; Salwani, I Sri; Lee, SY; Chin, HW; Faizal, R Ahmad; Tee, MK; Ridzwan, J Mohd; Phang, YR; et al. (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Melioidosis is caused by the gram negative bacillus Burkholderia pseudomallei and it is known to be endemic in the state of Pahang. Diabetes has been recognized as the main predisposing condition associated with melioidosis, hence it is timely to re-examine this association with disease severity, clinical course and outcomes. METHODOLOGY This was a retrospective study conducted in Hospital Sultan Haji Ahmad Shah, Temerloh in the state of Pahang recruiting all culture- positive Burkholderia pseudomallei patients aged 12 years old and older from January to December 2018. Data collected included demographics, co- morbidities, disease presentation, diabetes status, culture findings, complications, Quick Sequential Organ Failure assessment score (qSOFA), antibiotic usage and disease outcomes. Data obtained were analysed using SPSS Version 26. RESULTS There were 39 patients were included in this study, with a mean age of 52.1 years (± 14.1). Pre-existing or newly-diagnosed diabetes was noted in 66.7% (n=26). Of these patients, 25% had systemic inflammatory response syndrome (SIRS) and 35.9% had severe sepsis or septic shock. High qSOFA score at presentation was seen in 17.9% of patients with diabetes. The diagnosis of melioidosis was based on positive blood cultures in 89%; almost 30% had pulmonary melioidosis. Majority (38.5%) received combination ceftazidime and sulfamethoxazole/ trimethoprim, while a third received Ceftazidime monotherapy presentation. Mortality rate in all patients with melioidosis treated in Temerloh was 30.8%; 80% of these patients had diabetes. CONCLUSION This study clearly demonstrated the impact of diabetes on severity of melioidosis infection and risk of mortality.